Pengembangan E-Magazine Biologi Berbasis SSI pada Materi Bioteknologi - Fuja Adinda Sinaga; Ummi Nur Afinni Dwi Jayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop a Socio-Scientific Issues (SSI)-based biology e-magazine on Biotechnology material for tenth-grade students at SMA Taman Siswa Pematang Siantar that is valid, practical, and effective in supporting students' conceptual understanding. The novelty of this study lies in the integration of five socioscientific issues spanning local to global scales, namely bioethanol in Papua, GMO food safety, COVID-19 vaccines, designer babies, and de-extinction, into a single e-magazine product for the senior high school level, distinguishing it from previous SSI-Biotechnology studies that were generally web-based or worksheet (LKPD)-based with a single issue. The method used was Research and Development (R&D) with the ADDIE development model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The product trial involved 25 tenth-grade students of SMA Taman Siswa Pematang Siantar, one biology teacher, and three expert validators comprising media, material, and SSI experts. The results showed that the e-magazine obtained a very valid category, with assessment percentages of 94% from the media expert, 92% from the material expert, and 94% from the SSI expert. The practicality test showed a very practical response from students at 92% (n=10) and from the teacher at 94% (n=1). The effectiveness test showed an increase in students' conceptual understanding, with the average pretest score of 34.8 increasing to 88.4 on the posttest (n=25) and an N-Gain value of 0.82, categorized as high. The study concludes that the developed SSI-based e-magazine meets the criteria of validity, practicality, and effectiveness in supporting the improvement of students' conceptual understanding on tenth-grade Biotechnology material. Keywords: Biotechnology, Conceptual Understanding, E-Magazine, Research and Development, Socio-Scientific Issues